The Silence of the Kulikovo Field - Lidin, Konstantin (project baikal, 2016)
The notion of landscape is closely related to classifying and sense-making perception.  The presence of an architectural object can drastically change the semantic field of the landscape. The museum complex “The Battle of Kulikovo Field” transforms a typical mid-Russian steppe landscape into an object filled with historical, mythological, ideological and other senses. As a result, a natural object becomes an object of text and book urban culture.
Keywords: landscape; architecture; nature; city; sense making